A Bibliometric Review of Sustainable Development in the Hospitality Sector - OLAWUYI, Olakunle S.; KLEYNHANS, Carina (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025, 2025)
The hospitality industry essentially provides accommodation and lodging facilities to its guests. This industry generates significant revenue for many countries. Sustainable development depicts the current generation’s responsible usage of valuable items, so that future generations can have access and explore the items. Data for this research was collected from Scopus repository. The time range for the data collected is between 2015-2025. It is notable that the search for the data on Scopus identified a total of 717 documents, but 710 documents were found to be eligible for this study, as shown in the Prisma flow chart. The data collected was analysed with biblioshiny package in R studio. The result revealed that the Journal of Sustainability (Switzerland) had done significantly well by leading other journals with respect to a number of publications on sustainable development. Na Na is the most prolific scholar with twenty-four articles. The scholarly output with the most influence vis-à-vis total citations is in the Journal of Sustainable Tourism, published by Han H., 2021, with a total of 440 citations and a total of citations per year of 88.0. The result was underpinned with Sustainable Development Goal (SDG) 6 and 12.